Impact of Training Program Components on Perceived Training Utility and cGMP Compliance Behavior: An Evidence from Pharmaceutical Industry (Pakistan) (Journal of Asian Development Studies, 2025)
This study investigates the impact of training need assessment, training design, and trainer competence on cGMP compliance behavior, both directly and through the mediation of employee-perceived training utility, in the Pakistani pharmaceutical industry. Primary data were collected from a sample of 412 employees using Likert scale-based measures adapted from cGMP training parameters. The hypothesized relationships were tested using SPSS. The results show that training needs assessment, training design, and trainer competency have significant positive direct effects on perceived utility of training (PUOT) and cGMP compliance behavior. It was also found that PUOT partially mediates the relationships between all three training variables and cGMP compliance behavior, suggesting that the training program components play a vital role in fostering cGMP compliance behavior directly, and through perceived training usefulness.The research expands empirical work on training and compliance, asserting the need to ensure systematic training need assessment, well-structured and valid training design, and trainers’ competencies to foster cGMP compliance behavior among pharma employees, thereby improving training utility perception and regulatory compliance outcomes.